2015
DOI: 10.5194/acp-15-8165-2015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and formation mechanism of continuous hazes in China: a case study during the autumn of 2014 in the North China Plain

Abstract: Abstract. Four extreme haze episodes occurred in October 2014 in the North China Plain (NCP). To clarify the formation mechanism of hazes in autumn, strengthened observations were conducted in Beijing from 5 October to 2 November. The meteorological parameters, satellite data, chemical compositions and optical properties of aerosols were obtained. The hazes originated from the NCP, developing in the southwest and northeast directions, with the highest concentration of PM2.5 of 469 μg m−3 in Beijing. The NCP wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(132 citation statements)
references
References 38 publications
11
119
2
Order By: Relevance
“…The large increase in the concentrations and contributions of SNA during the haze process was observed in many previous studies and is mainly attributed to enhanced secondary conversions via enhanced heterogeneous reactions under relatively high humidity conditions during the haze periods ( Fig. S6; averaging 67 % during haze episodes and 37 % during clean periods in summer in Beijing, as measured in this study; Huang et al, 2016;Yang et al, 2015). The degree of the secondary formation of sulfate and nitrate is commonly estimated using the sulfur oxidation ratio (SOR = n-SO 2− 4 /n-SO 2− 4 + n-SO 2 , where n refers to molar concentration) and the nitrogen oxidation ratio (NOR = n-NO − 3 /n-NO − 3 +n-NO 2 ), respectively X.…”
Section: Evolution Of Chemical Componentsmentioning
confidence: 84%
See 3 more Smart Citations
“…The large increase in the concentrations and contributions of SNA during the haze process was observed in many previous studies and is mainly attributed to enhanced secondary conversions via enhanced heterogeneous reactions under relatively high humidity conditions during the haze periods ( Fig. S6; averaging 67 % during haze episodes and 37 % during clean periods in summer in Beijing, as measured in this study; Huang et al, 2016;Yang et al, 2015). The degree of the secondary formation of sulfate and nitrate is commonly estimated using the sulfur oxidation ratio (SOR = n-SO 2− 4 /n-SO 2− 4 + n-SO 2 , where n refers to molar concentration) and the nitrogen oxidation ratio (NOR = n-NO − 3 /n-NO − 3 +n-NO 2 ), respectively X.…”
Section: Evolution Of Chemical Componentsmentioning
confidence: 84%
“…In this study, the SOR and NOR were significantly elevated during the increases in PM 2.5 concentrations in the summer period and remained at a high level during haze episodes in Beijing (averaging 0.92 for SOR and 0.38 for NOR), Tianjin (0.83 and 0.41),and Shijiazhuang (0.65 and 0.44). In autumn, Yang et al (2015) also revealed that the intense secondary formation of SNA contributed most to the formation of the hazes in October 2014, with the SOR and NOR values increasing considerably during the haze episodes. Similar variations were also observed in winter, but the formation of SNA in winter was much weaker than that in summer and autumn, with SOR values of only 0.18-0.35 and NOR values of 0.20-0.22 during the regional haze episode (13 to 15 January) at the three urban sites.…”
Section: Evolution Of Chemical Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atmospheric NO − 3 and SO 2− 4 are mainly from secondary formation via heterogeneous, multiphase or gasphase reactions, which are dependent on the concentrations of their precursors (NO 2 and SO 2 ) and OH radicals, the surface characteristics and areas of particles, and RH (Ravishankara, 1997; Wang et al, 2013;Quan et al, 2014;Nie et al, 2014;He et al, 2014;Yang et al, 2015;. The remarkably higher concentrations of NO 2 , SO 2 and PM 2.5 at BD, WD and DBT compared to BJ (Table 2) densities, and thus residential coal combustion might also make an evident contribution to atmospheric pollutants at BJ.…”
Section: Chemical Composition Of Pm 25 At the Four Sampling Sitesmentioning
confidence: 99%